Estimating the insertion length of pediatric peripherally inserted central catheters. Issue 1 (26th May 2022) - Ota, Hidehito; Ide, Kentaro; Watanabe, Taro; Nishimura, Nao; Nakagawa, Satoshi
Abstract: Background: It is difficult to determine the insertion length of peripherally inserted central catheters (PICCs) without fluoroscopy. The objectives of this study were to examine the relationship between the length from the anterior axillary point to the level of the carina (Lcarina ) and patient's height, and to obtain possible estimation formulas that can be considered for validation in future studies. Methods: We retrospectively analyzed PICCs from the upper arm in the pediatric intensive care unit (PICU) between May 2017 and September 2018. We evaluated the relationship between Lcarina and the patient's height using linear regression. We also conducted simulated performance assessment of simplified formulas based on the observed relationships. Results: Fifty‐four PICCs from the right arm and 49 from the left for patients at the median age of 1 year were analyzed. The following linear correlations between Lcarina and the patient's height were observed: 0.105 × height (cm) + 1.53 (cm) ( P < 0.001, R 2 = 0.71) from the right arm, and 0.125 × height (cm) + 1.21 (cm) ( P < 0.001, R 2 = 0.65) from the left arm. In the simulated performance assessment, with a simplified formula, [0.1 × height (cm) + 1 (cm)], 93% (50/54) of the PICCs from the right arm and 96% (47/49) from the left arm were expected to be inserted in the subclavian vein, innominate vein, or superior vena cava. Conclusions: The level of the carina was correlated with the patient's height. A simplified formula, 0.1 × height (cm) + 1, seemed to perform acceptably and appeared to be worth validating in future studies.